Rancangan Sistem Aplikasi Edukasi Augmented Reality Mengenal Daerah Nusantara Indonesia Berbasis Android Menggunakan Unity - Dede Handayani; Ajeng Permata Suri (JURIKOM (Jurnal Riset Komputer), 2022)
Along with the times, science is growing and increasingly studied. Science is usually summarized in a book which is often called an encyclopedia. The explanation in the book only contains two-dimensional theory and images. By applying Augmented Reality, making cultural recognition applications will be more interesting. Displays 3D images taken from 2D images so that they appear more vivid images. The application of Augmented Reality also encourages children to get to know culture more through interesting learning. It is hoped that students' proficiency in learning will rise with the help of this program. Based on the test results using Augmented Reality, it can be concluded that in order to get good results the user is asked to place the picture book in a flat place. This application does not succeed in displaying objects if the markerless is uneven